Review Cultural Representations of Gender Vulnerability and Resistance: A Mediterranean Approach to the Anglosphere - Torres-Fernández, J. Javier (Miscelánea: A Journal of English and American Studies, 2023)
Reseña de Cultural Representations of Gender Vulnerability and Resistance: A Mediterranean Approach to the Anglosphere (2022) editado por María Isabel Romero-Ruiz and Pilar Cuder-Domínguez.